Coordination of mastication, swallowing and breathing - Koichiro Matsuo; Jeffrey B. Palmer (Elsevier, 2009)
The pathways for air and food cross in the pharynx. In breathing, air may flow through either the nose or the mouth; it always flows through the pharynx. During swallowing, the pharynx changes from an airway to a food channel. The pharynx is isolated from the nasal cavity and lower airway by velopharyngeal and laryngeal closure during the pharyngeal swallow. During mastication, the food bolus accumulates in the pharynx prior to swallow initiation. The structures in the oral cavity, pharynx and larynx serve multiple functions in breathing, speaking, mastication and swallowing. Thus, the fine temporal coordination of feeding among breathing, mastication and swallowing is essential to provide proper food nutrition and to prevent pulmonary aspiration. This review paper will review the temporo-spatial coordination of the movements of oral, pharyngeal, and laryngeal structures during mastication and swallowing, and temporal coordination between breathing, mastication, and swallowing.